Dual specificity phosphatase-1 as a pharmacogenetic modifier of inhaled steroid response among asthma patients - Jin, Ying (2010)
BACKGROUND: Inhaled corticosteroids (ICS) are considered first-line treatment for persistent asthma; yet, there is significant variability in treatment response. Dual specificity phosphatase-1 (DUSP1) appears to mediate the anti-inflammatory action of corticosteroids. OBJECTIVE: To determine whether variants in the DUSP1 gene are associated with clinical response to ICS treatment. METHODS: Study participants with asthma were drawn from the following multi-ethnic cohorts: the Genetics of Asthma in Latino Americans (GALA) study, the Study of African Americans, Asthma, Genes & Environments (SAGE), and the Study of Asthma Phenotypes and Pharmacogenomic Interactions by Race-ethnicity (SAPPHIRE). We screened GALA participants for genetic variants that modified the relationship between ICS use and bronchodilator response. We then replicated our findings in SAGE and SAPPHIRE participants. In a group of SAPPHIRE participants treated with ICS for 6 weeks, we examined whether a DUSP1 polymorphism was associated with changes in forced expiratory volume at one second (FEV(1)) and self-reported asthma control. RESULTS: DUSP1 polymorphisms, rs881152 and rs34507926, localized to different haplotype blocks and appeared to significantly modify the relationship between ICS use and bronchodilator response among GALA participants. This interaction was also seen for rs881152 among SAPPHIRE, but not SAGE participants. Among the group of SAPPHIRE patients prospectively treated with ICS for 6 weeks, rs881152 genotype was significantly associated with changes in self-reported asthma control but not FEV(1). CONCLUSION: DUSP1 polymorphisms were associated with clinical response to ICS therapy, and therefore, may be useful in the future to identify asthma patients more likely to respond to this controller treatment. CLINICAL IMPLICATIONS: These findings further our understanding of ICS pharmacogenetics and will hopefully result in improved tailoring of this controller therapy among individuals with asthma and in better disease control. CAPSULE SUMMARY: We identified genetic variants in DUSP1 which appeared to mediate the clinical response to inhaled corticosteroid (ICS) medication. These findings may eventually assist in identifying individuals with asthma most likely to respond this controller therapy.